Has the Growth in "Fast Casual" Mexican Restaurants Impacted Weight Gain? - Osea Giuntella (Institute of Labor Economics (IZA), 2018)
The United States is witnessing a boom in fast casual restaurants owing to the recent growth of ethnic restaurants throughout the country. This study examines the effects of proximity to a Mexican restaurant – the dominant type of ethnic fast casual restaurant – on maternal and child health. I match data on the complete residential addresses of all mothers who gave birth in the Miami metropolitan area between 1990 and 2009 to a time series of all establishments (restaurants and stores) selling food and drink. This unique data set allows me to use mother fixed effects and to exploit the variation over time of the food environment to identify the effects on maternal weight gain and childbirth outcomes. The results show that living in proximity to a Mexican restaurant is associated with an 8% lower likelihood of excessive weight gain among US-born mothers. These effects are concentrated in low-income neighborhoods and among members of disadvantaged groups (e.g., low-skilled, young, and African- American individuals). However, the results show no protective effect for foreign-born mothers. Lastly, there is no evidence of significant effects on other maternal outcomes or on various child health metrics at birth.
Keywords: I10; J1; R20; 330; restaurant proximity; food environment; maternal weight gain